1990
DOI: 10.1037/0735-7044.104.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Lexical priming deficits as a function of age.

Abstract: The effects of age on implicit memory were assessed in elderly and young adults using 2 priming procedures. Subjects also completed the WAIS-R, 3 tests to assess frontal lobe function, and 2 recall and 2 recognition tests of explicit memory. In Experiment 1, subjects were exposed to the low-frequency member of a homophone pair in a test purported to assess general knowledge. Subsequently, subjects completed a spelling test that contained the previously presented homophones to assess priming. Young subjects dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
104
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 46 publications
12
104
1
Order By: Relevance
“…According to Winocur and his colleagues, older participants perform poorly on WSC because of inefficient search strategies that decrease the utility of a perceptual cue in defining a set of possible target items (Winocur et al, 1996). Supporting this hypothesis, Davis et al (1990) found that lower WSC priming in older adults was associated with poor performance on the Wisconsin Card Sorting Test, a test of rule learning that requires strategy, flexibility, and inferential learning (see also Winocur et al, 1996).…”
Section: Search and Selection Processes In Implicit Andsupporting
confidence: 50%
See 1 more Smart Citation
“…According to Winocur and his colleagues, older participants perform poorly on WSC because of inefficient search strategies that decrease the utility of a perceptual cue in defining a set of possible target items (Winocur et al, 1996). Supporting this hypothesis, Davis et al (1990) found that lower WSC priming in older adults was associated with poor performance on the Wisconsin Card Sorting Test, a test of rule learning that requires strategy, flexibility, and inferential learning (see also Winocur et al, 1996).…”
Section: Search and Selection Processes In Implicit Andsupporting
confidence: 50%
“…At least five investigations using word-stem completion (WSC) have found decreased priming in older adults when compared with young adults (Chiarello & Hoyer, 1988;Davis et al, 1990;Hultsch, Masson, & Small, 1991;Schacter, Church, & Osowiecki, 1994, Experiment 1;Small, Hultsch, & Masson, 1995;Winocur, Moscovitch, & Stuss, 1996), although at least an equal number of studies have found no age-related differences in priming (Dick, Kean, & Sands, 1989;Java & Gardiner, 1991;Light & Singh, 1987;Park & Shaw, 1992;Schacter et al, 1994, Experiment 2). In contrast, reliable age differences in priming are consistently absent in word-fragment completion (Light, Singh, & Capps, 1986;Rybash, 1994;Winocur et al, 1996), lexical decision (Balota & Ferraro, 1996;Karayanidis, Andrews, Ward, & McConaghy, 1993), and word identification (Hashtroudi, Chrosniak, & Schwartz, 1991;Light & Kennison, 1996;Light, LaVoie, ValenciaLaver, Albertson-Owens, & Mead, 1992;Light & Singh, 1987; but see Abbenhuis, Raajmakers, Raajmakers, & Van Woerden, 1990).…”
mentioning
confidence: 99%
“…Studies in which priming in healthy older adults has been examined have found either intact priming (Howard, Fry, & Brune, 1991;Java & Gardiner, 1991;Light, La Voie, Valencia-Laver, Albertson Owens, & Mead, 1992;Light & Singh, 1987;Mitchell,1989;Moscovitch,1982) or small age-related deficits (Chiarello & Hoyer, 1988;Davis et al, 1990;Fleischman & Gabrieli, 1998;Hultsch, Masson, & Small, 1991;Schacter, Church, & Osowiecki, 1994), suggesting that this phenomenon, unlike deliberate retrieval, is largely immune to aging. Findings that overall repetition priming effects are relatively constant across age groups do not, however, unequivocally support the assumption that the processes that produce these effects are entirely age insensitive.…”
mentioning
confidence: 99%
“…Humans display marked decrements in performance on PFCdependent tasks with ageing, similar to those observed in monkeys. For example, Davis et al (1990) observed age-related impairments in performance on the Stroop Interference and Wisconsin Card Sort tests, even at relatively early stages in the ageing process. Thus, the ability of a 2 -agonists to improve performance of PFC-dependent tasks in aged monkeys suggests the possibility that these drugs may be of benefit in the treatment of cognitive decline associated with ageing in humans.…”
Section: Discussionmentioning
confidence: 99%